ANALISIS DETERMINAN KINERJA PEGAWAI DINAS SOSIAL KABUPATEN SUMBAWA: JOB DESCRIPTION DAN JOB SPECIFICATION - Kamal, Afina Aurellya; Kamaruddin, K; Cahyani, Helda Dwi (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to know the effect of job descriptions and job specifications on employee performance at Social Department of Sumbawa District. The type of this study was associative study which aims to determine the effect of job descriptions (X1) and job specifications (X2) on employee performance at Social Department of Sumbawa District. The type of data used was quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 32 employees at Social Department of Sumbawa District. Determination of respondents using non-probability sampling techniques with the census sampling method (saturated sampling). The data used in this study was processed using the SPSS application to be analyzed using multiple linear regression analysis techniques, partial hypothesis test (t test), simultaneous hypothesis test (F test), and coefficient of determination test (R2). The results of this study showed that job descriptions and job specifications had a positive and significant effect on employee performance at Social Department of Sumbawa District, both partially and simultaneously. The contribution of job description and job specification in effecting employee performance at Social Department of Sumbawa District was 73.2%, while the remaining of 26.8% was effected by other variables not examined in this study, such as work environment, job satisfaction, and organizational commitment.